2019
DOI: 10.1002/bjs5.50184
|View full text |Cite
|
Sign up to set email alerts
|

Survey of surgical training and experience of associate clinicians compared with medical officers to understand task‐shifting in a low‐income country

Abstract: BackgroundA workforce crisis exists in global surgery. One solution is task‐shifting, the delegation of surgical tasks to non‐physician clinicians or associate clinicians (ACs). Although several studies have shown that ACs have similar postoperative outcomes compared with physicians, little is known about their surgical training. This study aimed to characterize the surgical training and experience of ACs compared with medical officers (MOs) in Tanzania.MethodsAll surgical care providers in Pwani Region, Tanza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The general shortage of physicians, especially in rural areas, yielded difficulties in ensuring the supervision of NSCs during training and operations [44, 50]. To address this problem, associate clinicians and medical officers supervised and taught each other during operations in Tanzania [50]. The degree of supervision is questionable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general shortage of physicians, especially in rural areas, yielded difficulties in ensuring the supervision of NSCs during training and operations [44, 50]. To address this problem, associate clinicians and medical officers supervised and taught each other during operations in Tanzania [50]. The degree of supervision is questionable.…”
Section: Resultsmentioning
confidence: 99%
“…One study reported ongoing supervision of 9 months and a 94.4% compliance rate of supervision in the first year after training [35]. In contrast, another study reported that less than three-fifths of trainees met the required number of ''performed under supervision'' cases [50].…”
Section: Supervision (N = 3)mentioning
confidence: 99%
“…A goal-directed approach that aims to achieve a grade of expertise is far more reliable than depending on a case log alone [ 32 ]. The mere number of procedures conducted cannot be equated with mastery and is only a poor surrogate at best [ 33 ]. Making proficiency the primary requirement for board certification would emphasize the individualization of training, which has proven to be cost effective and appropriate in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…14 The quality of surgical care in Tanzania by AMOs and medical doctors was similar, 13 and both groups reported similar training experiences and post-training challenges. 15 In addition to task sharing, Dr. Mbaruku recommended the simultaneous upgrade of existing, mostly rural, health centers with operating theaters, critical renovations, equipment, and supplies. This meant that health providers could perform all critical EmONC services on location, rather than referring women with life-threatening complications to hospitals several hours away.…”
Section: Program To Reduce Maternal Deaths In Tanzaniamentioning
confidence: 99%